Molecular mechanisms of intrauterine growth restriction. (2nd October 2018) - Gurugubelli Krishna, Rao; Vishnu Bhat, B.
Abstract: Intrauterine growth restriction (IUGR) is a pregnancy specific disease characterized by decreased growth rate of fetus than the normal growth potential at particular gestational age. In the current scenario it is a leading cause of fetal and neonatal morbidity and mortality. In the last decade exhilarating experimental studies from several laboratories have provided fascinating proof for comprehension of molecular basis of IUGR. Atypical expression of enzymes governed by TGFβ causes the placental apoptosis and altered expression of TGFβ due to hyper alimentation causes impairment of lung function. Crosstalk of cAMP with protein kinases plays a prominent role in the regulation of cortisol levels. Increasing levels of NOD1 proteins leads to development of IUGR by increasing the levels of inflammatory mediators. Increase in leptin synthesis in placental trophoblast cells is associated with IUGR. In this review, we emphasize on the regulatory mechanisms of IUGR and its associated diseases. They may help improve the in-utero fetal growth and provide a better therapeutic intervention for prevention and treatment of IUGR.